Buyers' workload and R&D procurement outcomes: Evidence from the US Air Force Research Lab - Leonardo M. Giuffrida; Emilio Raiteri (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2021)
Does workload constitute a bottleneck to a public agency's mission, and if so, to what extent? We ask these questions in the context of the US government's procurement of R&D. We link tender, contract, patent, and office records to the identity of the officer responsible for the procurement process to estimate how workload in the federal acquisition unit affects the execution of R&D contracts. The identification comes from unanticipated retirement shifts among contracting officers, which we use to instrument workload. We find a large increase in patenting at the extensive margin when the same officer is exposed to a declining workload. In our sample, an additional contracting officer in the procurement unit, holding fixed the procurement budget and number of purchases, leads to a two percentage point increase in the probability for an R&D contract to generate patents. We provide suggestive evidence that backlogged contracting officers are unable to devote enough time to tender and contract specifications.
Keywords: D23; H57; O31; O32; 330; Workload; Public Procurement; Contracting Officer; R&D; Patents